Diferenciacion de razas del virus de la tristeza de los citricos (CTV) mediante hibridacion molecular - Albiach, M.R.=700 1 Rubio, L.; Guerri, J.; Moreno, P.; Laigret, F.; Bove, J.M.
(Es, En)
ilus., 32 ref.
Keywords: CLONACION; HIBRIDACION MOLECULAR; RESERVAS GENETICAS; ESPAÑA; DNA; RNA